2001
DOI: 10.2337/diabetes.50.6.1464
|View full text |Cite
|
Sign up to set email alerts
|

The Antihyperglycemic Drug α-Lipoic Acid Stimulates Glucose Uptake via Both GLUT4 Translocation and GLUT4 Activation

Abstract: The cofactor of mitochondrial dehydrogenase complexes and potent antioxidant ␣-lipoic acid has been shown to lower blood glucose in diabetic animals. ␣-Lipoic acid enhances glucose uptake and GLUT1 and GLUT4 translocation in 3T3-L1 adipocytes and L6 myotubes, mimicking insulin action. In both cell types, insulin-stimulated glucose uptake is reduced by inhibitors of p38 mitogen-activated protein kinase (MAPK). Here we explore the effect of ␣-lipoic acid on p38 MAPK, phosphatidylinositol (PI) 3-kinase, and Akt1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
129
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(138 citation statements)
references
References 48 publications
5
129
1
3
Order By: Relevance
“…Treatment of islets with 2.0 mmol/l α-LA (a concentration similar to that used in other in vitro studies [8,9]) for 15 min led to an increase in phosphorylation of the AMPK α-subunit at Thr172 (2.54±0.14 fold) compared with untreated islets (p<0.001) (Fig. 1a,b).…”
Section: Activation Of Ampk Signallingmentioning
confidence: 52%
See 1 more Smart Citation
“…Treatment of islets with 2.0 mmol/l α-LA (a concentration similar to that used in other in vitro studies [8,9]) for 15 min led to an increase in phosphorylation of the AMPK α-subunit at Thr172 (2.54±0.14 fold) compared with untreated islets (p<0.001) (Fig. 1a,b).…”
Section: Activation Of Ampk Signallingmentioning
confidence: 52%
“…Bitar et al [5] demonstrated that α-LA could partly ameliorate insulin resistance in type 2 diabetic rats, while others had reported additional antidiabetic effects in earlier rodent [4,6], and human studies [7]. In vitro approaches have also shown that α-LA can enhance glucose disposal in skeletal muscle [8] and adipocytes [9], and suppress hepatic gluconeogen-esis [10]. The exact molecular mechanisms responsible for these effects are currently not known.…”
mentioning
confidence: 99%
“…The stimulation of glucose uptake would supply substrate for this increased demand on glycolysis. Troglitazone rapidly (in 30 min) stimulates 2-deoxyglucose uptake into muscle cells [16], and hence we were intrigued by a potential connection between stimulation of glucose uptake by troglitazone and its effect on mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…It is remarkable that stimuli that increase p38 phosphorylation such as insulin-like growth factor-1 (18), muscle contraction (19 -21), lipoic acid (22), 5-aminoimidazole-4-carboxamide ribonucleoside (23), pro-inflammatory cytokines (18), protein synthesis inhibitors (24, 25), hyperosmolar stress (26), and preconditioning (ischemia/reperfusion) (27) also elevate glucose uptake. Importantly, the pyridinylimidazole inhibitor of p38, SB203580, reduced the stimulation of glucose uptake by all of the above stimuli including insulin in skeletal muscle and/or various cell lines, suggesting that p38 may be a component in the signaling pathway leading to the stimulation of glucose uptake (18,19,22,23,25,28).Insulin stimulates glucose uptake in mature skeletal muscle, adipose tissue, and insulin-responsive cells in culture by recruiting glucose transporter 4 (GLUT4) to the plasma membrane. Interestingly, although SB203580 reduced insulin-mediated glucose in 3T3-L1 adipocytes and L6 muscle cells, it did not diminish GLUT4 translocation to the plasma membrane (13,14).…”
mentioning
confidence: 99%